2014
DOI: 10.1002/jso.23590
|View full text |Cite
|
Sign up to set email alerts
|

Australian multi‐center experience outside of the Sydney Melanoma Unit of isolated limb infusion chemotherapy for melanoma

Abstract: In this, to date, largest multi-center study of ILI for melanoma the results are comparable to other reports and demonstrate that ILI can be widely implemented and safely applied across tertiary referral centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Comparing ILP/ILI patients diagnosed with melanoma to those with STS, the melanoma patients were slightly older (mean 64 years for melanoma and 59 years for STS), consistent with previous reports of age at the time of procedure for each disease . The mean LOS (4.8 days) following ILP/ILI for melanoma in the current study was most consistent with what is reported in the literature for ILI .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Comparing ILP/ILI patients diagnosed with melanoma to those with STS, the melanoma patients were slightly older (mean 64 years for melanoma and 59 years for STS), consistent with previous reports of age at the time of procedure for each disease . The mean LOS (4.8 days) following ILP/ILI for melanoma in the current study was most consistent with what is reported in the literature for ILI .…”
Section: Discussionsupporting
confidence: 89%
“…Comparing ILP/ILI patients diagnosed with melanoma to those with STS, the melanoma patients were slightly older (mean 64 years for melanoma and 59 years for STS), consistent with previous reports of age at the time of procedure for each disease. [7][8][9][10]12,13,18,37,[39][40][41] The mean LOS (4.8 days) following ILP/ILI for melanoma in the current study was most consistent with what is reported in the literature for ILI. 42,43 The mean LOS for the STS patients who underwent ILP/ILI was slightly longer (7.0 days), and may suggest a higher proportion of patients undergoing ILP, which is typically associated with a longer LOS.…”
Section: Perioperative Outcomessupporting
confidence: 85%
See 2 more Smart Citations
“…4 ILI has been extensively investigated for unresectable recurrent melanoma within large, randomized prospective studies. [5][6][7] Complete and partial response (PR) rates have been consistently reported between 24% to 38% and 22% to 40%, respectively, with median overall survival (OS) periods of up to 44 months. 8,9 Predictors of response to ILI using local data have also been described by Barbour et al 10 More recently, intralesional Rose Bengal (PV-10) has been studied for locoregionally advanced and metastatic melanoma.…”
mentioning
confidence: 99%